Rupture of mitral chordae tendineae: adding to the list of hypertension complications. Issue 12 (15th February 2009) - Juang, J J-M; Ke, S-R; Lin, J-L; Hwang, J-J; Hsu, K-L; Chiang, F-T; Tseng, C-D; Tseng, Y-Z; Chen, J-J; Hu, F-C; Lin, Y-T; Lai, L-P
Abstract : Background: Many patients with chordae tendineae rupture (CTR) of the mitral valve have obscure aetiologies. The association between pre-existing hypertension and idiopathic CTR was investigated. Methods: 494 patients with CTR were identified by searching the computer database. For each patient with idiopathic CTR, three matched controls without CTR who were admitted to the same hospital for bone fractures were included. Results: Among the 494 patients with CTR, 351 patients (71%) had idiopathic CTR, and 143 patients (29%) had secondary CTR. The prevalence of pre-existing hypertension was significantly higher in the idiopathic than in the secondary CTR group (50.9% vs 14.6%, p<0.001). The odds ratio was 6.0 (95% CI 3.6 to 10.1). The percentage of patients without adequate blood pressure control was also higher in the idiopathic than in the secondary CTR group (23.1% vs 4.9%, p<0.001). When compared with the fracture group, patients with idiopathic CTR also had a significantly higher prevalence of hypertension (50.9% vs 14.9%, p<0.001), and the odds ratio was 5.9 (95% CI 4.5 to 7.8). After correction for age, the odds ratio of having hypertension was 3.6 (95% CI 2.1 to 6.3) and 6.6 (p<0.001, 95% CI 5.0 to 8.8) when compared with the secondary CTR group and fracture group respectively. Conclusions: There is a strong association between pre-existing hypertension and idiopathic CTR. Whether or not this disease can be prevented by controlling hypertension deserves further investigation.